2021
DOI: 10.3390/su131910650
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Common Agricultural Policy in Europe: A Bibliometric Analysis

Abstract: The last few years have been marked by the increasing attention paid by policymakers to agricultural policies. Within this scenario, the Common Agricultural Policy represents one of the main initiatives developed by the European Commission to enhance the agricultural sector. Academics have actively contributed to the debate through empirical studies in order to evaluate the main strengths and weakness related to the public investments made by the European Commission. However, despite the relevance of the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Bibliometric analysis is a scientific method commonly used to explore new fields. Keywords co-occurrence analysis is a popular analysis method in bibliometric, which can effectively identify the structural characteristics of knowledge [ 67 , 68 , 69 ]. According to the keywords co-occurrence network, we found that the main research topics in the field of long COVID can be roughly divided into the following four aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis is a scientific method commonly used to explore new fields. Keywords co-occurrence analysis is a popular analysis method in bibliometric, which can effectively identify the structural characteristics of knowledge [ 67 , 68 , 69 ]. According to the keywords co-occurrence network, we found that the main research topics in the field of long COVID can be roughly divided into the following four aspects.…”
Section: Discussionmentioning
confidence: 99%
“…MerigÓ et al ( 2016 ) and Markard et al ( 2012 ) weighted the most citation in an absolute term that means the total citations of all time. According to Fusco ( 2021 ) and Essential Science Indicators, the most citation was weighted in a relative term, which means the citation number in the publication year. The top 1% papers, compared to other articles in the academic field published in the same publication year, were included in this study following the refining principle of Essential Science Indicators, ensuring that the impact of these articles does not fade with time.…”
Section: Methodsmentioning
confidence: 99%
“…A rigorous bibliometric analysis can provide systematic insights into previous publications, which can not only delve into the academic research community of active and influential researchers, but also identify the current research topics, and further explore potential directions for future research (Fahimnia et al, 2015 ). Bibliometrics has been widely applied in a wide range of sectors and specific domains, for example, mapping and visualizing the knowledge progress avenues and research collaboration patterns of cultural heritage (Vlase and Lähdesmäki, 2023 ), analyzing the sub-areas and core aspects of disease (Baskaran et al, 2021 ), visualizing and graphing the evolution of research related to sustainable development goals (Belmonte-Ureña et al, 2021 ), and studying policies, such as agricultural policy (Fusco, 2021 ), medical information policy (Yuxi et al, 2018 ), and science, technology and innovation policy (Zhang et al, 2016 ). However, the research trajectory and focus of policy analysis around the world remain a black box.…”
Section: Introductionmentioning
confidence: 99%
“…216 [27], [28], [29], [30] Data for producing maps of basic fertilizers 1600 [31] Data for production maps of fertilizer in the phenophase 30-34 3 -Data for determining heights of crops 846 [32], [33], [34], [35] Data for estimating the extent of diseases or damages (losses) 2 850 [36], [37] Data for monitoring hydrological stresses 426 [38], [39], [40] Data for producing exact information about climatic changes 2650 [18], [41], [42], [43], [44] Data for identification parcels for potential land for biomass production 146 -Data for creating flood maps (for Q5,25,50,100years) 1230 [45], [46], [47] Data for annual soil erosion risk maps 250 if special search "soil erosion" [48], [49] Data to produce maps of the occurrence of diseases 1750 special search [50], [51] Data for the production of actual calamities map (droughts, flood, fires, earthquakes, ...) 37 [45], [52], [53] Data for production maps of relevant information for biofuel production 248 [54], [55], [56], [57] Data for determining productivity of grassland and pastures. 205 [58], [59], [60] Data for support of the Common Agricultural Policy new 'greening' rules, crop, ecologically sensitive areas 127 [61] Data for the identification of crops to control subsidies 1110 -Data for water protection against nitrates 1130 …”
Section: Number Of Publications Analysed In Mdpi Most Relevant Papersmentioning
confidence: 99%